Virulence exaltation of Clostridium perfringens strains from bovines - Baldassi,L. (2004)
Ten out of eighty-nine strains biochemically identified as Clostridium perfringens, isolated from bovine organs, were selected by their different results showed in toxigenicity test on mice. Those and the standard strains, ATCC types A, B, C, and D, had their virulence exalted through serial intramuscular inoculation into guinea pigs. Results showed that, for toxigenic strains (6), one or two passages were enough to cause exaltation, while for the atoxigenic (4), five or six inoculations were needed. Esterase electrophoresis of standard and isolated strains, with and without exaltation, was performed. Electrophoresis analysis permits the following conclusions: strains that do not show any clinical symptoms in mice, when exalted demonstrate decreased esterase activity; on the contrary, it is increased when correlated with animal symptoms.